Les etats Unis de l'Amerique septentrionale, contenant en outre, les Isles Royale, de Terre Neuve, de St. Jean et l'Acadie, avec partie du Canada, de la Lousiane et de la Floride. - Bonne, Rigobert, 1727-1794. ([l'Abbe Grenet], 1781)
Relief shown pictorially. Depicts North American eastern seaboard from Florida to Nova Scotia, as well as the Bahamas and the tip of Cuba. Prime meridians: Paris and Isle de Fer.